2019
DOI: 10.1111/cas.14270
|View full text |Cite
|
Sign up to set email alerts
|

Mutation status and burden can improve prognostic prediction of patients with lower‐risk myelodysplastic syndromes

Abstract: Patients with lower-risk myelodysplastic syndromes (LR-MDS) as defined by the International Prognostic Scoring System (IPSS) have more favorable prognosis in general, but significant inter-individual heterogeneity exists. In this study, we examined the molecular profile of 15 MDS-relevant genes in 159 patients with LR-MDS using nextgeneration sequencing. In univariate COX regression, shorter overall survival (OS) was associated with mutation status of ASXL1 (P = .001), RUNX1 (P = .031), EZH2 (P = .049), TP53 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 44 publications
3
23
0
3
Order By: Relevance
“…Among them, three studies, including four cohorts, only provided Kaplan‐Meier curves (HRs extracted for OS as described above, which were regarded as universal HRs), and one study reported primary data that could be used to calculate the HR. As previously reported, 23 TP53 mutation was an adverse prognostic factor in MDS patients (HR = 2.59, 95% CI: 1.84‐3.63, P < .0001) from pooled limited data with high heterogeneity (I 2 = 86.5%) (Figure 2).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Among them, three studies, including four cohorts, only provided Kaplan‐Meier curves (HRs extracted for OS as described above, which were regarded as universal HRs), and one study reported primary data that could be used to calculate the HR. As previously reported, 23 TP53 mutation was an adverse prognostic factor in MDS patients (HR = 2.59, 95% CI: 1.84‐3.63, P < .0001) from pooled limited data with high heterogeneity (I 2 = 86.5%) (Figure 2).…”
Section: Resultssupporting
confidence: 75%
“…Numerous studies have already assessed the adverse prognostic effect of TP53 mutation in MDS, and the pooled HRs for OS in our present analysis confirmed the same view. However, recent studies have discovered that in these high‐risk patient subgroups, some patients still have relatively better survival and longer remission times 23 . In our meta‐analysis, results showed that patients with high VAF in TP53 mutant MDS had a shorter life expectancy than those with low frequency or no mutation.…”
Section: Discussionmentioning
confidence: 62%
“…The increased burden of somatic mutations in bone marrow samples has been associated with overall worse survival in patients with myeloid neoplasms [ 50 , 51 , 52 , 53 ]. Higher allele burden of somatic mutations in the CD34+ cells has been associated with overall more aggressive MDS sub-types [ 54 ] and congruence of the JAK2V617F CD34+ progenitor and neutrophil allele burdens in MPN patients has been correlated with more advanced disease and MF phenotype [ 55 ].…”
Section: Hypothesized Biologic Mechanisms Implicated In the Gendermentioning
confidence: 99%
“…Recently, JAK2 mutations have been reported to not only be associated with inferior survival in MDS receiving hematopoietic stem cell transplantation (HSCT) ( 28 ), but also in LR-MDS ( 29 ). JAK2 mutation leads to constitutive activation of the JAK2/STAT3 pathway which further resulted in growth factor independence, increased proliferation, and differentiation failure ( 30 ).…”
Section: Discussionmentioning
confidence: 99%